202 ft^2
The lateral area is the area of all the sides except the base. So you find the area of the triangles (16), then the left rectangle (80), then the right rectangle (90). Finally you add them together.
16+16+80+90=202
Answer: 0.29
Step-by-step explanation:
OQ is the side opposite angle P, QP is the side opposite angle O, and PO is the side opposite angle Q.
This means that tangent = opposite/adjacent, the tangent of angle O is the opposite side, QP, over the length of the adjacent side, OQ. (It cannot be PO since that's the hypotenuse)
This means that the tangent of O is 7/24, which is about 0.29
Answer:
<h3>
<u>Given Question</u></h3>
If
![\sf \: \dfrac{7}{x} + \dfrac{8}{y} = 2, \: \dfrac{2}{x} + \dfrac{12}{y} = 20, \: then \: x \: = \:](https://tex.z-dn.net/?f=%20%5Csf%20%5C%3A%20%5Cdfrac%7B7%7D%7Bx%7D%20%20%2B%20%5Cdfrac%7B8%7D%7By%7D%20%20%3D%202%2C%20%5C%3A%20%5Cdfrac%7B2%7D%7Bx%7D%20%20%2B%20%5Cdfrac%7B12%7D%7By%7D%20%20%3D%2020%2C%20%5C%3A%20then%20%5C%3A%20x%20%5C%3A%20%20%3D%20%20%5C%3A%20)
![\green{\large\underline{\sf{Solution-}}}](https://tex.z-dn.net/?f=%20%5Cgreen%7B%5Clarge%5Cunderline%7B%5Csf%7BSolution-%7D%7D%7D)
Given pair of equations are
![\rm :\longmapsto\:\dfrac{7}{x} + \dfrac{8}{y} = 2 - - - - (1)](https://tex.z-dn.net/?f=%5Crm%20%3A%5Clongmapsto%5C%3A%5Cdfrac%7B7%7D%7Bx%7D%20%20%2B%20%5Cdfrac%7B8%7D%7By%7D%20%20%3D%202%20-%20%20-%20%20-%20%20-%20%281%29)
and
![\rm :\longmapsto\:\dfrac{2}{x} + \dfrac{12}{y} = 20](https://tex.z-dn.net/?f=%5Crm%20%3A%5Clongmapsto%5C%3A%5Cdfrac%7B2%7D%7Bx%7D%20%20%2B%20%5Cdfrac%7B12%7D%7By%7D%20%20%3D%2020)
On dividing by 2, we get
![\rm :\longmapsto\:\dfrac{1}{x} + \dfrac{6}{y} = 10 - - - - (2)](https://tex.z-dn.net/?f=%5Crm%20%3A%5Clongmapsto%5C%3A%5Cdfrac%7B1%7D%7Bx%7D%20%20%2B%20%5Cdfrac%7B6%7D%7By%7D%20%20%3D%2010%20-%20%20-%20%20-%20%20-%20%282%29)
On multiply equation (1) by 3 and (2) by 4, we get
![\rm :\longmapsto\:\dfrac{21}{x} + \dfrac{24}{y} = 6 - - - - (3)](https://tex.z-dn.net/?f=%5Crm%20%3A%5Clongmapsto%5C%3A%5Cdfrac%7B21%7D%7Bx%7D%20%20%2B%20%5Cdfrac%7B24%7D%7By%7D%20%20%3D%206%20-%20%20-%20%20-%20%20-%20%283%29)
and
![\rm :\longmapsto\:\dfrac{4}{x} + \dfrac{24}{y} = 40 - - - - (4)](https://tex.z-dn.net/?f=%5Crm%20%3A%5Clongmapsto%5C%3A%5Cdfrac%7B4%7D%7Bx%7D%20%20%2B%20%5Cdfrac%7B24%7D%7By%7D%20%20%3D%2040%20-%20%20-%20%20-%20%20-%20%284%29)
On Subtracting equation (3) from (4), we get
![\rm :\longmapsto\: - \dfrac{17}{x} = 34](https://tex.z-dn.net/?f=%5Crm%20%3A%5Clongmapsto%5C%3A%20-%20%5Cdfrac%7B17%7D%7Bx%7D%20%20%20%3D%2034)
![\rm :\longmapsto\: - \dfrac{17}{34} = x](https://tex.z-dn.net/?f=%5Crm%20%3A%5Clongmapsto%5C%3A%20-%20%5Cdfrac%7B17%7D%7B34%7D%20%20%20%3D%20x)
![\bf\implies \:x \: = \: - \: \dfrac{1}{2}](https://tex.z-dn.net/?f=%5Cbf%5Cimplies%20%5C%3Ax%20%5C%3A%20%20%3D%20%5C%3A%20%20%20-%20%20%5C%3A%20%5Cdfrac%7B1%7D%7B2%7D%20)
▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬
<h3>
<u>Concept Used :- </u></h3>
There are 4 methods to solve this type of pair of linear equations.
1. Method of Substitution
2. Method of Eliminations
3. Method of Cross Multiplication
4. Graphical Method
We prefer here Method of Eliminations :-
To solve systems using elimination, follow this procedure:
<h3>
<u>The Elimination Method</u></h3>
Step 1: Multiply each equation by a suitable number so that the two equations have the same leading coefficient.
Step 2: Subtract the second equation from the first to eliminate one variable
Step 3: Solve this new equation for other variable.
Step 4: Substitute the value of variable thus evaluated into either Equation 1 or Equation 2 and get the value other variable.
Answer:
4, and -9
Step-by-step explanation:
Well, to solve this problem, lets first list all the factors of -36.
-36 = 1*(-36)
-36 = 2 * (-18)
-36 = 3 * (-12)
-36 = 4 * (-9)
-36 = 6 * (-6)
-36 = 12 * (-3)
-36 = 18 * (-2)
-36 = (-36) * 1.
So, we can see that 4 + (-9) = -5.
Let the numbers be x, x + 1 and x + 2.
From the information given:-
x(x + 1)(x + 2) = x^3 + 85
Solving for x:-
x(x^2 + 3x + 2) = x^3 + 85
x^3 + 3x^2 + 2x = x^3 + 85
3x^2 + 2x - 85 = 0
3x^2 - 15x + 17x - 85 = 0
3x(x - 5) + 17(x - 5) = 0
(3x + 17)(x - 5) = 0
x = -17/3 , 5
We take x = 5 because x is an integer.
Answer:- the 3 integers are 5, 6 and 7.